Notes on the genus Acosmetura Liu, 2000 (Orthoptera: Tettigoniidae: Meconematinae) - Bian, Xun; Kou, Xiao-Yan; Shi, Fu-Ming (Zootaxa, 2014)
This paper deals with one new species, Acosmetura mabianensis Bian & Shi sp. nov., one new combination, Acosmetura jinyunensis (Shi & Zheng, 1994) com. nov., and the first record of female of Acometura nigrogeniculata (Liu & Wang, 1998). Photographs of two known species, a key to the species, male stridulatory files and a distribution map are provided. We also observe the male stridulatory files and left tegmina for four known species of the genus. The material is deposited in the Museum of Hebei University.